Just a new neighbor - Mayer, Gina.; Mayer, Mercer 1943-. (New York Golden Books, 1999)
When new neighbors move in, Little Critter hopes they have kids his age. But when their kid turns out to be a girl, Little Critter is very disappointed.
"Mercer Mayer's Little Critter."
Keywords: Neighbors -- Fiction; Friendship -- Fiction